2006
DOI: 10.1248/bpb.29.1892
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-neurodegenerative Effects of Polygala tenuifolia in A.BETA.(25-35)-Treated Cortical Neurons

Abstract: The root of Polygala tenuifolia WILLD (PT) (Japanese name: Onji) is a well-known traditional Chinese medicine used as an expectorant, a tonic, a tranquillizer and an anti-dementia drug. However, basic researches of the anti-dementia effects are very few in spite of PT being generally recognized as a good herbal drug for amnesia. It was reported that 80% ethanol extract of PT and the methanol extract of PT reverse scopolamine-induced cognitive impairments in rats. 1,2) Acetylcholinestrase (AChE) activity is inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 23 publications
0
32
0
3
Order By: Relevance
“…We discovered that P3 protected primary cortical neurons against serum deficiency and glutamate-induced damage and PC12 cells against H 2 O 2 -induced death. Several researchers have demonstrated that Polygalae Radix extract provides neuroprotection of PC12 cells against 6-hydroxydopamine (6-OHDA)-induced damage and of primary cortical neurons against Aβ 25-35 -induced cell damage [24,25] . These results suggest that P3 may be effective in the treatment of various neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that P3 protected primary cortical neurons against serum deficiency and glutamate-induced damage and PC12 cells against H 2 O 2 -induced death. Several researchers have demonstrated that Polygalae Radix extract provides neuroprotection of PC12 cells against 6-hydroxydopamine (6-OHDA)-induced damage and of primary cortical neurons against Aβ 25-35 -induced cell damage [24,25] . These results suggest that P3 may be effective in the treatment of various neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan-Zhi has been used as a main ingredient in a TCM formula 'Kaixinsan' , which has shown clinical benefits for the treatment of insomnia, palpitations with anxiety, restlessness and disorientation (Howes and Houghton, 2003;Wang et al, 2007). Previous studies have demonstrated that Yuan-Zhi water extract has significant effects for neuroprotection in cultured cell model (Naito and Tohda, 2006) and improving learning memory of mice (Egashira et al, 2003). Yuan-Zhi ethanol extract is capable of reversing scopolamine-induced cognitive impairment by inhibiting acetylcholinesterase activity (Park et al, 2002;Ikeya et al, 2004), and improves stress-induced memory impairments through increment of glucose utilization and total neural cell adhesion molecule levels in rat brains (Shin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been renewed interest in the cognition-enhancing potential of P tenuifolia root extracts. Several studies have shown that P tenuifolia extracts have cognition improving effects in vivo, in addition to protective effects on neurotoxicity that is induced in vitro by factors such as glutamate, beta-amyloid, and the C-terminal fragment of amyloid precursor protein (CT) [2,[4][5][6] . However, the biologically active components from these extracts still require identification, and their in vivo functions and mechanisms must be understood before P tenuifolia root extracts can be developed into therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%